Euro Area Inflation : Aggregation Bias and Convergence - Byrne, Joseph P. (2012)
Monetary policy of the European Monetary Union targets aggregate euro area inflation. Concerns are growing that a focus on aggregate inflation may cause national inflation rates to diverge. While different explanations for diverging aggregate euro area inflation have been brought forward, the very impact of aggregation on divergence has, however, not been studied. We find a striking difference in convergence depending on the level of aggregation. While aggregate national inflation rates are diverging, disaggregate inflation rates are converging. We find that aggregation appears to bias evidence towards non-convergence. Our results are consistent with prominent theoretical and empirical evidence on aggregation bias.